Evaluation of hybrid corn genotype on productivity improvement to support national food availability. Issue 1 (April 2020) - Erawati, B T R; Hipi, A; Makkulawu, A T; Azrai, M
Abstract: Potential lines need to be tested to produce new superior varieties of hybrids with high yield potential to increase corn productivity. The purpose of the research is to produce a single cross-strain has the appearance of a good agronomist, double cob and high yield potential, as a candidate release of varieties. The study began in April to July 2018. Experimental site in the Lembar village, West Lombok Regency, West Nusa Tenggara Province. Eight crosses of a single cross-tested all showed the appearance of a good agronomist, in accordance with the criteria of belonging to four varieties comparison (Bisi-2, Nasa-29, HJ-21 and Bima-3). There is one the crosses cross-E2 x Mr14 was good combiner for double ear with the percentage exceeded 28% per ha. There are four single cross-E 2 X Mr 14, E 1 X Mr 14, E 65 X Mr 14, MS 3 X Mr 14, which has a high yield potential with the weight of the dried seeds > 13 ton/ha. There are four potential lines that can be released as a new high yielding varieties.